Perancangan Sistem Informasi Penerimaan Siswa Baru Berbasis Web Pada Lembaga Kursus dan Pelatihan Annisa Global Course - Yuliana Hutasuhut; Furqan Khalidy; Saiful Amir; Demonius Sarumaha; Mardiah (LKP Unity Academy, 2024)
New student admission is one of the processes of the system running in educational institutions such as schools to filter prospective students according to the criteria determined by the school. In research on new student admissions at the Annisa Global Course and Training Institute which has been done manually using brochures. Therefore, the system design that will be made is a web-based information system. With the times and the increasingly rapid development of science and technology. This web-based new student admission should be done. This information system development method applies the waterfall method. The website created has facilities to provide complete and fast information about LKP Annisa Global Course to users or registrants and facilitate the registration process. Then for the administrator or admin can do easy data processing.